Coordination of policy goals between renewable portfolio standards and carbon caps: A quantitative assessment in China. (1st March 2019) - Yi, Bo-Wen; Xu, Jin-Hua; Fan, Ying
Graphical abstract: Effective policy coordination interval between renewable portfolio standards (RPS) and carbon cap-and-trade policy. Highlights: Policy coordination between RPS and carbon cap-and-trade in China are evaluated. RPS and carbon caps have a very different impact on regional power sector. An effective policy mix interval by 2030 is estimated. The dependence of CO2 emission reduction policy on RES-E is examined. Abstract: China has planned to implement renewable portfolio standards (RPS) and national carbon cap-and-trade to promote the low-carbon transformation of society. How to design and coordinate the goals of these policies becomes a key issue. This study quantitatively evaluates the effects of RPS and carbon caps in China's power sector using a multi-regional power optimization model combining with decomposition method. Based on the framework, this study focuses on two questions: (1) How to coordinate policy goals of RPS and carbon caps to ensure the effectiveness of each policy in the face of policy overlapping? (2) How to design power generation and transmission planning to achieve the goals of different policy mixes? Results show that these two policies contain overlapping elements, yet remain different impacts on regional power structures, inter-regional power and coal dispatches. An effective policy interval for RPS and carbon caps is estimated to examine the effectiveness of any policy mixes. If an RPS with a 17% non-hydro renewable share is implemented by 2030, the effective interval of carbon caps will be between a 27.5% and 38.2% reduction in carbon intensity. Results support that there are strong inner linkages between reasonable power system planning and current status of policy mix.